Critical review on resource scheduling in IaaS clouds : Taxonomy, issues, challenges, and future directions - Madni, Syed Hamid Hussain; Faheem, Muhammad; Younas, Muhammad; Masum, Maidul Hasan; Shah, Sajid (John Wiley & Sons, 2024)
In a cloud computing environment, the primary goal of resource scheduling is to reduce the economic expenditures for cloud users and grow fiscal achievement for cloud providers. In this article, the study of numerous forms of resource scheduling algorithms is presented that has been applied in IaaS clouds. The selected research articles are classified into six categories, according to the nature of the algorithm used. Further, the authors pointed out several issues and challenges with the help of the resource scheduling algorithms, the comparative performance metrics, and the simulation tools used to validate the several algorithms. The enhancement illustrates better performance concerns decreasing the cost and time while improving the competence and utilization of resources for IaaS clouds. These algorithms are executed in numerous simulation tools and real environments similar to CloudSim, SimGrid, MATLAB, and test-bed environments (practical implementation). This critical review and classification will serve as a foundation for further research in IaaS clouds in the Internet of Things (IoT) environments.
Keywords: peer-to-peer computing; cloud computing; fog computing; pervasive computing; internet of things; fi=Tietotekniikka|en=Computer Science|